The equation of a line has the form:
y=mx+b
We can find m by means of the formula:
![m=(y2-y1)/(x2-x1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/wt3vklmulg2853jxzclws9uvfaplhmpgv7.png)
Where (x1,y1) and (x2,y2) are points of the line.
In this case, we have the points (6,-10) and (-4,10), then we get:
![m=(10-(-10))/(-4-6)=(10+10)/(-10)=(20)/(-10)=-(20)/(10)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/6crga3yq546qmm6t4cx0w5wl3b0iq9zbb8.png)
Now that we know that m= -2, we only need to find b, we can do it like this:
by taking the point (6,-10) replacing it into the equation and solving for b, we get:
-10 = -2*(6) + b
-10 = -12 + b
-10 +12 = b
b = 2
Then, the equation of this line is:
![y=-2x+2](https://img.qammunity.org/2023/formulas/mathematics/high-school/cto8ugstveuqjkjzh3u4o7k19mw8z9zla1.png)